Per Capita Income Convergence among Provinces in China - Di Wang; Zhimin Wang; Yuying Xie (International Journal of Economics and Financial Issues, 2020)
One increasingly important political and economic challenge of China's economy is income inequality. In the past two decades, a series of regulations and policies were enacted to promote its economic growth and reduce income inequality. In this empirical study, we examine the effectiveness of these regulations and policies on reducing the personal income gap at the provincial level in China and analyze the reasons behind the effectiveness: education expenses, infrastructure investments, and fixed asset investments. We test the per capita income data of 31 provinces over the periods 1999 to 2018 and our results show that the per capita income converges nationally and in most regions. The convergence in per capita income is supported by the convergence in per capita education expenses, infrastructure investments, and fixed asset investments. Without fundamental changes in economic policies, the current economic growth may not be sustainable. Our paper suggests that continuously increase investments in education expenses, infrastructure investments, and fixed asset investments in poor regions are necessary to reduce the income gap between rich and poor regions to foster long-term prosperity.